There is no difference in nitric oxide metabolites and neonatal outcome between premature infants born to pre-eclamptic and those born to normotensive women - Suppo de Souza Rugolo, Ligia Maria [UNESP]; Almeida de Sa, Milene Piorkowsky [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Madoglio, Rosa Juliana [UNESP]; Bentlin, Maria Regina [UNESP]; Rugolo, Antonio [UNESP]; Corrente, Jose Eduardo [UNESP] (Maney Publishing, 2015)
Background: The pathophysiology of pre-eclampsia (PE) is complex, and nitric oxide (NO) may be a factor. The neonatal outcome in pregnancies complicated by PE is controversial, and the PE/NO/neonatal diseases relationship has not been well established.Aims: To measure nitrate and nitrite levels in the placenta, umbilical cord blood, blood and urine of preterm neonates born to pre-eclamptic and normotensive women and to investigate the relationship between placental, fetal and neonatal NO metabolites and neonatal outcome.Methods: A prospective study was undertaken of 30 preterm infants,34 weeks of gestation, born to preeclamptic mothers and matched by gestational age with 30 infants born to normotensive mothers. Samples from the placental tissue, venous cord blood and the newborns'blood on day 4 and urine on days 1 and 4 were assayed for NO metabolites (nitrate and nitrite). Clinical variables and NO metabolites were compared between the groups. Generalised linear models were fitted to associate NO metabolites levels with adverse neonatal outcomes.Results: There were no differences in NO metabolites and neonatal outcomes between the two groups. Increased levels of NO metabolites were found in the placenta and cord blood of small-for-gestational-age infants, and in the cord blood of newborns with necrotising enterocolitis and those who died.Conclusion: NO metabolite levels in the placenta and fetal and neonatal circulation were not associated with PE; however, cord blood levels of NO metabolites differed according to fetal growth and neonatal outcome.
Keywords: Nitric oxide; Pre-eclampsia; Infant; Premature; Neonatal outcome